Interaction of Eukaryote Elongation Factor EF 1 with Guanosine Nucleotides and Aminoacyl-tRNA - Moon, Hong-Mo (1972)
Evidence for two species of elongation factor 1 (EF 1(A) and EF 1(B)) from calf brain has been obtained by molecular sieve chromatography on Sephadex G-150. A high molecular weight form, EF 1(A), interacts with GTP to form an EF 1(A)-GTP complex. GDP also reacts with EF 1, but unlike the reaction with GTP, an EF 1(B)-GDP complex is formed that contains a lower molecular weight and labile species of EF 1. The results also indicate that EF 1(A)-GTP reacts with aminoacyl-tRNA to form an aminoacyl-tRNA-EF 1(B)-GTP complex. These results are discussed with regard to the role of EF 1 in aminoacyl-tRNA binding to ribosomes.